Development strategy of home broadband IPTV service - Yingxia NIU; Xin HE (Dianxin kexue)
In the aspect of service,the biggest difference between IPTV business and internet TV business is IPTV business can provide live business,but in the aspect of system deployment,the requirements of cloud platforms,pipelines,terminals and other parts of the network are different.The development form of TV service and the construction mode of service platform was introduced.The transformation strategy of network and equipment because the operators carried out IPTV business were analyzed from the aspects of platform,CDN,metropolitan area network,converged transmission,PON access,end-to-end multicast,end-to-end QoS and video terminal.